Postnatal weight gain in the first two weeks as a predicting factor of severe retinopathy of prematurity requiring treatment - Kim, Jongmoon; Jin, Jang Yong; Kim, Sung Shin (Clinical and experimental pediatrics, 2015)
This study aimed to investigate the relative weight gain at 2-week intervals up to 6 weeks after birth to predict retinopathy of prematurity (ROP) requiring treatment among very low birth weight infants. A total of 211 preterm infants with birth weights <1,500 g and gestational age <32 weeks were retrospectively reviewed. The main outcome was the development of ROP requiring treatment. Body weight measurements were recorded daily. Relative weight gains (g/kg/day) were calculated at the second, fourth, and sixth week after birth. Of the 211 infants, 89 developed ROP, of which 41 spontaneously regressed and 48 with early treatment of ROP type I required laser treatment. The relative weight gain at 2, 4, and 6 weeks postnatal age was significantly lower in infants with ROP requiring treatment than in infants without ROP or those with spontaneous regression (P<0.001, P=0.005, and P=0.004, respectively). On logistic regression, poor relative weight gain in the first 2 weeks was found to be related to ROP requiring treatment (adjusted odds ratio, 0.809; 95% confidence interval, 0.695-0.941; P=0.006). Relative weight gain at 2 weeks postnatal age was significantly lower in infants with ROP requiring treatment compared to that in ROP requiring no treatment (P=0.012). Poor postnatal weight gain in the first 2 weeks of life is an important and independent risk factor for ROP requiring treatment. Postnatal weight gain can predict the development of severe ROP requiring treatment.